Vertical track stiffness effect on dynamic behaviour of track structure - Milan Moravcik (Communications - Scientific letters of the University of Zilina, 2004)
The dynamic modelling of railway track response and of the interaction of vehicle and track at low and mid frequencies that are significant for the track deterioration, is presented. The response of the track subjected to a moving vehicle is simulated for a stationary randomly distributed ballast stiffness with a standard uniform distribution and a normal distribution. The response of the track components is solved by the Finite Element Method. Monte Carlo simulation was applied to estimate the dynamic track response. The dynamic amplification resulting from the simulated passage of the locomotive of the type E 499 (85 t) is presented.